Use of an ex vivo canine ventral slot model to test the efficacy of a piezoelectric cutting tool for decompressive spinal surgery. Issue 7 (5th August 2013) - Farrell, Michael; Solano, Miguel A.; Fitzpatrick, Noel; Jovanovik, Jelena
Abstract Objective To test the efficacy of a piezoelectric instrument (PI) for bone removal during ventral slot surgery. Study Design Ex vivo feasibility study. Sample Population Cadaveric canine cervical spinal specimens (n = 3; C1–7; C1–T1; C2–T1). Methods The spinal cord of each explanted spinal unit was replaced with a saline‐filled latex condom. In 8 disc spaces, ventral slot surgery was performed using a previously reported technique. Bone removal was achieved using a motorized burr (MB). In 8 disc spaces, bone was removed via en bloc ostectomy with a PI that selectively cuts mineralized tissue. Surgical duration and operating field visibility were recorded. Rupture of the fluid filled condom was used as a measure of iatrogenic collateral trauma. Computed tomography was used to measure ventral slot morphometry. Results Mean surgical duration for PI (23.4 minutes) was significantly shorter than for MB (34.1 minutes; P = .049). Using a 4 point Likert scale (4 = excellent, 3 = good, 2 = fair, 1 = poor), median visibility score was significantly higher for PI (2) than for MB (1; P = .03). The condom burst twice (1MB, 1PI) during elevation of the dorsal longitudinal ligament; there was no significant difference between techniques for incidence of collateral trauma (P = .99). Regardless of surgical technique, there was a bias in slot deviation towards the right (i.e., the surgeon's left; P = .021). Conclusions The PI allowed completion of ventral slots in a significantly shorter time, without an increased incidence of iatrogenic trauma. The right‐handed surgeon showed a left‐sided aiming bias, regardless of surgical technique.